Obesity during pregnancy: a study on the repercussions on the life of the mother-newborn binomial (Research, Society and Development, 2023)
Pregnancy is considered a moment of great joy for women, while requiring essential care. The objective of this work is to analyze in the scientific literature the problems related to obesity during pregnancy for the mother-child binomial. This is an integrative literature review, for which the Virtual Health Library (VHL) was used, with articles from the LILACS, MEDLINE and BDENF databases, using the health descriptors (DeCS) "Pregnancy" and "Obesity”. A total of 82 articles were found, from which, after filtering and reading the abstracts, 10 of them were selected that were consistent with the theme in question. Articles written in Portuguese and English, available in full, during the period from 2016 to 2021 and that fit the chosen theme, prior to 2016 and that were not available in full or that did not converge with the theme in question, were included. The results showed that obesity can cause serious problems for the mother and the child, in the long and short term. For the mother, there is a risk of gestational diabetes, pre-eclampsia, hypertensive disease specific to pregnancy, in addition to cesarean sections and risk of maternal mortality; for the conceptus: large for gestational age, macrosomia, and perinatal/fetal mortality. Therefore, it is the role of nursing to guide these women before conception on issues related to their nutrition, and during prenatal care to provide advice on healthy eating patterns along with systematic monitoring, so that weight gain is adequate for both involved.